2001
DOI: 10.1523/jneurosci.21-17-06846.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Modulation of Behavioral and Neuronal Correlates of Repetition Priming

Abstract: In this experiment we address the pharmacological modulation of repetition priming, a basic form of learning, using eventrelated functional magnetic resonance imaging. We measured brain activity in a word-stem completion paradigm in which, before study, volunteers were given either placebo, lorazepam (2 mg orally), or scopolamine (0.4 mg, i.v.). Relative to placebo, both drugs attenuated the behavioral expression of priming. Repetition was associated with a decreased neuronal response in left extrastriate, lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 52 publications
6
56
1
Order By: Relevance
“…Several studies in healthy young and older subjects suggest that fMRI can detect acute pharmacological effects on memory networks (Thiel et al 2001;Sperling et al 2002;Kukolja et al 2009). To date, only a few small fMRI studies have shown enhanced brain activation after acute or prolonged treatment with cholinesterase inhibitors in MCI and AD, although these studies were not conducted as typical double-blind, placebocontrolled trials (Rombouts et al 2002;Goekoop et al 2004;Saykin et al 2004;Shanks et al 2007;Bokde et al 2009;Venneri et al 2009).…”
Section: Utility Of Functional Mri In the Study Of Admentioning
confidence: 99%
“…Several studies in healthy young and older subjects suggest that fMRI can detect acute pharmacological effects on memory networks (Thiel et al 2001;Sperling et al 2002;Kukolja et al 2009). To date, only a few small fMRI studies have shown enhanced brain activation after acute or prolonged treatment with cholinesterase inhibitors in MCI and AD, although these studies were not conducted as typical double-blind, placebocontrolled trials (Rombouts et al 2002;Goekoop et al 2004;Saykin et al 2004;Shanks et al 2007;Bokde et al 2009;Venneri et al 2009).…”
Section: Utility Of Functional Mri In the Study Of Admentioning
confidence: 99%
“…Moreover, there is growing support for the hypothesis of the central role of the GABAergic system in neuronal plasticity required for repetition adaptivity (34,35). Yet the genes involved in the GABA turnover in the brain have never been systematically investigated as candidate genes for dyslexia.…”
mentioning
confidence: 99%
“…In healthy volunteers, behavioural and fMRI repetition effects are strongly attenuated with lorazepam, suggesting that GABAergic and cholinergic systems influence the neuronal plasticity necessary for repetition priming (Thiel, Henson, Morris, Friston, & Dolan, 2001). Conversely, facilitated processing of internal and external stimuli in anxiety has been linked to excessive excitability of cortical cholinergic inputs from the basal forebrain (Berntson, Sarter, & Cacioppo, 1998).…”
Section: Priming In Ocdmentioning
confidence: 99%